2009
DOI: 10.1002/jor.21006
|View full text |Cite
|
Sign up to set email alerts
|

Synoviocytes are more sensitive than cartilage to the effects of minocycline and doxycycline on IL-1α and MMP-13-induced catabolic gene responses

Abstract: The objective of this study was to determine the primary articular tissue target of doxycycline and minocycline. Synoviocytescartilage cocultures (n ¼ 4) were treated with MMP-13 (25 ng/mL medium) or IL-1 (1.0 ng/mL medium) for 24 h. Doxycycline (4.3, 0.43, 0.043 mM) or minocycline (10, 1.0 or 0.1 mM) were then added and cultures were continued for 96 h. Cartilage and media were analyzed for GAG content. Quantitative PCR was used to measure cartilage MMP-3, MMP-13, aggrecan, COL2A1, ADAMTS-4, and ADAMTS-5 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…The in vitro data also showed that doxycycline exhibited a dose dependent reduction of MMP-13 gene expression as well as protein expressions by day-21 of pellet culture. This is consistent with the MMP-13 suppressing activity of doxycycline found in other differentiated tissue types, such as chondrocytes and synoviocytes 7, 9 . However, doxycycline-mediated inhibition of mmp-13 expression occurred earlier after 24-hours of doxycycline exposure in other studies on chondrocytes 9, 10 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The in vitro data also showed that doxycycline exhibited a dose dependent reduction of MMP-13 gene expression as well as protein expressions by day-21 of pellet culture. This is consistent with the MMP-13 suppressing activity of doxycycline found in other differentiated tissue types, such as chondrocytes and synoviocytes 7, 9 . However, doxycycline-mediated inhibition of mmp-13 expression occurred earlier after 24-hours of doxycycline exposure in other studies on chondrocytes 9, 10 .…”
Section: Discussionsupporting
confidence: 88%
“…Because we did not find any differences in aggrecan and col-II mRNA expression levels among pellets cultured in different doxycycline concentrations, this effect is more likely due to improved matrix retention through inhibition of MMP-13 production. As MMP-13 primarily functions to break down collagen-II 7, 23 , MMP-13 downregulation would ultimately lead to reduction of excessive collagen-II degradation or enhancement of collagen-II accumulation. MMP-13 is also a marker of terminal differentiation of MSCs into hypertrophic chondrocytes 23, 34, 35 .…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 and MMP-9, also known as gelatin A and gelatin B, play crucial roles in angiogenesis [39][41].They degrade type IV collagen, which forms the filamentous structure and basement membranes. Previous studies have shown that minocycline could inhibit the activity of MMP- 2, -3, -8, -9, -12, and -13 [42][44]. In our study, the mRNA and protein levels of MMP-2, and MMP-9 and mRNA levels of MMP-13 were significantly reduced after administration of minocycline (60 mg/kg b.i.d.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, the highest mean synovial fluid trough concentration previously reported for doxycycline in a similar study was 181.78% of the corresponding trough plasma concentration [21]. In addition, this value is markedly higher than the 0.046 mg/ml of minocycline reported to be chondroprotective in vitro through reduction of GAG loss into the media and reduction of MMP-3, MMP-13 and basal ADAMTS-5 mRNA expression as well as reduction of active MMP-13 protein levels [16]. Although the minocycline concentration in synovial fluid (0.33 Ϯ 0.12 mg/ml) was lower than our previous study that examined doxycycline, these minocycline concentrations are high enough to inhibit the growth of susceptible bacteria.…”
Section: Discussionmentioning
confidence: 59%
“…Higher protein binding may limit tissue distribution of doxycyline to a greater extent than minocycline. Minocycline also has more potent anti-catabolic effects in cartilage and synovium than doxycycline, suggesting that minocycline may have a role in the treatment of equine joint disease [16]. In previous studies, doxycycline had limited penetration into the AH and CSF and was not detected in either fluid when administered orally at a dose of 10 mg/kg bwt q.…”
Section: Introductionmentioning
confidence: 99%